Validity and reliability of the Iranian force plate - Sepideh Latifi; Elham Shirzad; Narges Pirmohammadi; Mojtaba Gohari (Sport Sciences and Health Research)
Background: Force plates are widely used in biomechanics and sports sciences to measure various aspects of human movement. The accuracy and reliability of force plate measurements are critical for valid data interpretation.Aim: The purpose of the study was to evaluate the validity and reliability of the Iranian force plate in the vertical, anterior-posterior, and medial-lateral directions using two manual dynamometers and a load cell.Materials and Methods: In this study, the force plate device utilized had a frequency of 1200 Hz and was manufactured by the Danesh Salar Iranian Company. Additionally, to determine the device's validity, we used Lafayette hand-held dynamometers manufactured in the United States and a load cell by Zemik. Pearson's correlation coefficient was employed to determine the validity of the force plate, while the internal consistency coefficient (ICC) was used to assess the force plate's reliability.Results: The study findings indicated a significant and high level of reliability between the maximum force obtained from the force plate device and manual dynamometer devices and load cell. Additionally, the internal consistency coefficient was found to be excellent (very high) for 20 trials in the three directions of vertical (0.98), anterior-posterior (0.96), and medial-lateral (0.97).Conclusion: The study demonstrated that the Iranian force plate is a reliable device for measuring maximum force in the three directions of vertical, anterior-posterior, and medial-lateral, with very high validity.